"Red, White, Yellow, Blue, All Out but You": Status Effects on Team Formation, an Expectation States Theory. (June 2016) - Skvoretz, John; Bailey, Jasmón L.
Teams are ubiquitous in contemporary business, government, health care, and education settings; hence, the process of team formation is worth close examination. We propose models based in expectation states theory for the probability that a particular candidate (or subset of candidates) is selected from a pool of potential team members who are differentiated along diffuse status characteristics. The candidates may be equally qualified in other respects, but the ways in which they differ will be activated under specified conditions and influence their chances of selection. We use the "motherhood penalty" literature to illustrate the model and the inferences it affords. Our concluding discussion notes that although a step forward in understanding team selection, the model cannot be the whole story as "suitability, " a legitimate consideration in the team formation process, is unaddressed by an expectation states based model focused solely on attributions of competence as the drivers of teammate choice.